Legal Liability of Artificial Intelligence in Healthcare: A Comparison of Indonesia and Germany - Aji Widayat; Muhammad Endriyo Susila (Prodi Tata Negara (Siyasah) IAIN Langsa, 2026)
This article examines legal liability for the use of Artificial Intelligence (AI) in healthcare services using normative, conceptual, and comparative approaches between Indonesia and Germany, and based on the theory of Patient-Centered Care, which places patients as the primary subject of legal protection. The results show that AI integration can improve diagnostic quality, service efficiency, and health data management, but also poses various legal risks, such as unclear subject liability due to system autonomy, potential data privacy violations, algorithmic bias, and difficulties in proving due to the black box nature. Furthermore, a liability gap phenomenon has emerged, demonstrating the limitations of traditional legal regimes in accommodating the complexity of medical AI, particularly in the distribution of legal liability between medical personnel, healthcare institutions, and technology developers. In the regulatory context, Indonesia still faces legal fragmentation and the absence of specific regulations on AI in the healthcare sector, potentially creating a legal vacuum and weak patient protection. In contrast, Germany and the European Union have developed a more comprehensive regulatory framework through a risk-based approach, transparency, and legal liability, including strengthening data protection and legal liability mechanisms. Therefore, this study recommends the development of specific and integrated AI regulations in Indonesia, the implementation of a multi-layered and risk-based accountability model, and the strengthening of oversight and ethical standards to ensure patient protection and legal certainty in the use of AI in healthcare.